Comparisons of Mechanical Properties of sub-mm Lead Based and Lead Free Based Solder Using in Manufacturing of Printed Circuits - Ali, Alaa Hasan (Al-Khwarizmi Engineering Journal, 2017)
AbstractThis study investigates the mechanical compression properties of tin-lead and lead-free alloy spherical balls, using more than 500 samples to identify statistical variability in the properties in each alloy. Isothermal aging was done to study and compare the aging effect on the microstructure and properties.The results showed significant elastic and plastic anisotropy of tin phase in lead-free tin based solder and that was compared with simulation using a Crystal Plasticity Finite Element (CPEF) method that has the anisotropy of Sn installed. The results and experiments were in good agreement, indicating the range of values expected with anisotropic properties.Keywords: Lead-free solder, composite solder, and aging.